Temperature Sensitivity and Soil Organic Carbon Pools Decomposition under Different Moisture Regimes: Effect on Total Microbial and Enzymatic Activity. Issue 3 (2nd July 2014) - Hassan, Waseem; Bano, Rizwana; Khatak, Bashir Ullah; Hussain, Imtiaz; Yousaf, Mohummad; David, Julie
<x xml:space="preserve">Abstract</x> The soils of the world store significantly more carbon than present in the atmosphere. However, there is still no consensus regarding the effects of climate change, i.e. increase in temperature on global soil carbon stocks. An incubation experiment was conducted under a temperature range (5–45°C) and moisture conditions, i.e. U1–U5 (20–100% water‐holding capacity) with the objective to investigate temperature sensitivity of labile and recalcitrant organic carbon pools, total microbial activity, and soil extracellular enzymes, i.e. phenol oxidase and catalase activity in an Ultisol soil. The maximum increase in the labile organic carbon pool, i.e. water soluble organic carbon (3.52‐fold), microbial biomass carbon (2.31‐fold), readily mineralizable carbon (6.16‐fold), permanganate oxidized organic carbon (2.81‐fold), and reducing sugar carbon (3.97‐fold) was observed at 35°C, whereas the effect at other temperatures was in the order 25 > 45 > 15 > 5°C. The total organic carbon (TOC) tended to decrease with the increased temperature (from 5–35°C), therefore, maximum TOC (14.7 g kg−1) was observed at 5°C, and minimum (1.76 g kg−1) at 45°C. Conversely, the highest increase (6.48‐fold) in the recalcitrant organic carbon pool was noticed at 45°C, and the impact of other temperatures was in the order 35 > 25 > 15 > 5°C. The maximum increase in the total microbial activity (13.68‐fold) and soil enzymes, phenol oxidase and catalase (3.94 and 3.98‐fold, respectively) activity was observed at 35°C, while the influence of other temperature ranges was in the order 25 > 45 > 15 > 5°C. The effect of moisture regimes on the temperature sensitivity of organic carbon pools, total microbial and enzymatic activity was in the order U3 > U4 > U2 > U1 > U5.